IMPLEMENTASI METODE YANBUA DALAM MENINGKATKAN KUALITAS BACAAN AL-QURAN SANTRI DI PONDOK PESANTREN MAMBAUL HIKAM JATIREJO DIWEK JOMBANG - M Syafi’ Syauqillah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
SYAUQILLAH, SYAFI, M. 2024. “Implementation of the Yanbua Method in Improving the Quality of Al-Quran Reading of Students at the Mambaul Hikam Jatirejo Diwek Jombang Islamic Boarding School”. Islamic Religion Undergraduate Education Program, Hasyim Asy'ari Tebuireng University, Jombang”, Supervisor: Dr. Ali Said, M.HI Islamic boarding schools are traditional Islamic educational institutions in Indonesia that place little emphasis on comprehensive religious learning. Students are led by a kyai or ustadz and are educated in the Qur'an, hadith, fiqh, and other Islamic activities. Some Islamic boarding schools combine formal education with religious education, and some also use technology in their educational process. Islamic boarding schools play a role in maintaining Islamic identity and shaping the character of students. Mambaul Hikam Jatirejo Diwek Jombang Islamic boarding school uses the Yanbua method in teaching the Qur'an, attracting the attention of scholars to study the implementation of the Yanbua method in improving the quality of students' reading of the Qur'an at the Mambaul Hikam Jatirejo Diwek Jombang Islamic boarding school.Based on the problems above, this study has 2 targets related to the focus of the research Implementation of the Yanbua Method in Improving the Quality of Students' Reading of the Qur'an at the Mambaul Hikam Jatirejo Diwek Jombang Islamic boarding school. The objectives of this study are one, To explain the implementation of the Yanbua Method in improving the quality of students' reading of the Qur'an at the Mambaul Hikam Jatirejo Diwek Jombang Islamic boarding school. Two, To find out the inhibiting and supporting factors of the implementation. The Yanbua Method in improving the quality of students' reading of the Qur'an at the Mambaul Hikam Jatirejo Diwek Jombang Islamic boarding school.This study uses a qualitative method, and the type of research used is descriptive research. The data were collected through interviews, observations, and documentation. In this study, informants consisted of Al-Qur'an teachers and students. To analyze data from observations and interviews, the triangulation analysis method of data sources was used. The following are the results of a study on the use of the Yanbua method to improve the quality of students' reading at the Mambaul Hikam Islamic boarding school: 1) the application of the Yanbua method at the Mambaul Hikam Islamic boarding school, namely implementing it according to the first Yanbua book; second, students read the teacher, then imitate him; and third, the teacher reads the students after they listen. 2) Supporting and inhibiting factors for the Yanbu'a method include teachers who have participated in the program, facilities and infrastructure, and lack of motivation for students to learn the Qur'an. This program aims to improve the quality of students' Al-Qur'an reading by using the Yanbua method.